2016
DOI: 10.1002/2016jc012294
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive upwelling in the Central Great Barrier Reef

Abstract: In the Central Great Barrier Reef, the outer continental shelf has an open reef matrix that facilitates the exchange of waters with the Coral Sea. During austral summer, cool water intrudes onto the shelf along the seafloor. Temperature observations reveal cool, bottom intrusions during a 6 year period from the Queensland Integrated Marine Observing System's Palm Passage mooring. A metric is used to identify 64 intrusion events. These intrusions predominantly occur from October to March including the wet seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…1 and 2 could potentially have been impacted by upwelling events that occur mostly from October to March (summer), when the south‐easterly trade winds relax and monsoon winds are active. However, a recent study (Benthuysen et al ), which characterized upwelling events in the GBR over the period 2010–2015, did not detect any events within the weeks of our sampling times and an impact on our results therefore seems unlikely.…”
Section: Resultsmentioning
confidence: 57%
“…1 and 2 could potentially have been impacted by upwelling events that occur mostly from October to March (summer), when the south‐easterly trade winds relax and monsoon winds are active. However, a recent study (Benthuysen et al ), which characterized upwelling events in the GBR over the period 2010–2015, did not detect any events within the weeks of our sampling times and an impact on our results therefore seems unlikely.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, near‐surface warming increases the stratification, reducing vertical mixing with deeper oceanic waters, and potentially changing the depth of upwelling waters and nutrient sources (García‐Reyes et al, ). For 2016, in the Central GBR, typical upwelling events appeared to have been suppressed during the peak of the MHW, compared with past years during the same month (Benthuysen et al, ). The Slocum gliders revealed that the warm waters were found from midshelf to the shelf break over hundreds of kilometers and even in the reef passages known for intrusive upwelling (Figures c and d).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…As they traversed the continental shelf and through reef passages, the glider temperatures revealed that the warm waters extended throughout the water column (Figures c and d). In the reef passages off Townsville, the typical March outer‐shelf temperatures can be cooler by up to several degrees along the bottom due to intrusive upwelling or well‐mixed with the transition into April with the seasonal breakdown of the stratification (Benthuysen et al, ). Intrusive upwelling has been associated with weakening or a reversal in the southeasterly winds during the monsoon season (Benthuysen et al, ).…”
Section: Evolution Of the Marine Heatwavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future projections along the SE coast of Australia suggest a decrease of downwelling favorable winds [Sen Gupta et al, 2016, Figure S5]. This might lead to shallower MHWs, while local persistent upwelling [Lourenço et al, 2016] or intrusive bottom uplift [Benthuysen et al, 2016] could provide respite from ocean warming and new habitat for some species.…”
Section: Discussionmentioning
confidence: 99%